"Is your leadership creating value or harm?" - Mohammad Sopian, NorAin; Pitchay , Anwar Allah (International Journal of Accounting, Finance and Business, 2026)
Top management commitment (TMC) is widely recognised as a key driver of organisational performance and innovation capability. However, existing literature primarily focuses on economic outcomes, with limited attention to ethical and societal dimensions. This viewpoint paper integrates the concept of Maslahah (public welfare) into TMC, arguing that leadership should not only drive performance but also guide organisations toward socially responsible outcomes. By positioning Maslahah as a guiding principle, the paper reframes leadership as a force that shapes resource allocation, organisational culture, and decision-making in ways that promote both innovation and public welfare. It proposes that Maslahah aligns internal capabilities with societal needs, enhancing long-term sustainability and organisational relevance. The study contributes by extending the resource-based view with an ethical perspective and provides practical insights for leaders seeking to balance competitiveness with social responsibility.